Water content dynamics in a volcanic ash soil slope in southern Chile. Issue 4 (2nd July 2015) - Dörner, José; Huertas, Jenny; Cuevas, Jaime G.; Leiva, César; Paulino, Leandro; Arumí, José L.
Abstract Andisols present exceptional physical properties, making up < 1% of the world's soils. While there is a lot of information about non‐volcanic soil properties, research about soils of volcanic origin is limited. Specifically, no major studies have been carried out to improve our knowledge of these soils' hydrological behavior, which is relevant due to the impact of climate change on water resources and to the soil's role in the hydrological cycle. Thus, the aim of this work was to analyze the water content dynamics of a soil slope derived from volcanic ashes under different land covers. We hypothesized that land cover, rainfall, and air temperature, in addition to the hydraulic properties of the volcanic ash soil, regulate the slope's water content dynamics. Our study was conducted in S Chile, in a fluvial terrace covered by pastures in the uplands, a native forest in the adjacent slope, and a hygrophilous forest in the floodplain at the base of the slope, surrounding a stream. Soil physical properties, such as bulk density (Db), volume of macropores (wCP), plant available water (PAW) and saturated hydraulic conductivity (Ks) were studied. Rainfall, air temperature, volumetric water content (θField) and soil temperature were continuously measured with data loggers. The groundwater level was also measured. Water content dynamics reflect the behavior of rainfall and air/soil temperatures under different land covers, as well as, revealing the specific behavior of volcanic soil's pore system (e.g., Db < 0.9 Mg m−3). Soil depths exposed to more intensive and dynamic wetting and drying cycles presented well‐defined water release ranges as compared to the pore system of deeper soil horizons. Soils present large water holding capacities (PAW > 24%), however, during summer they can reach volumetric water contents near to the permanent wilting point quickly at a depth of 5 cm. The water table altitude was directly related to the temporal changes of θField measured at a depth of 50 cm, highlighting the fact that the saturated and unsaturated zones are connected.